Evidentiary Review of Screening Infants for Autism - Jones, Mary Kay; Lauver, Lori (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Autism is a severe developmental disorder that affects a child’s communication, social, and repetitive behaviors. Typically a child will be diagnosed with autism around the age of three. Identifying an autistic child younger than three can be performed at the child’s well visits, through the evaluation of the child’s developmental milestones. Multiple screening tools have been developed and used to facilitate the identification of developmental milestones. Currently these tools used are for children aged 18 months and older. There is a need to identify a screening tool or tools to be used for infants, (i.e., under 18 months of age) who fail to achieve developmental milestones. The goal of this evidentiary review is to explore the screening tools for infants between the ages of 9 and 18 months.